Solve the system of equations.
6x + 2y = 10 and -6x - 2y = 12: (A) (0, 5)
(B) (-1, 8)
(C) (2, -1)
(D) no solution
(E) infinitely many solutions

dclark|Points 60|

Question|Asked by renaryoko

Asked 4/2/2014 3:46:36 AM

Updated 4/22/2014 7:38:34 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [4/22/2014 7:38:34 PM]

Rating

3

6x + 2y = 10;

-6x - 2y = 12

Adding up the above equations we have:

0 = 22 which is not true.

Therefore, there is NO SOLUTION for the system of equations 6x + 2y = 10 and -6x - 2y = 12.

-6x - 2y = 12

Adding up the above equations we have:

0 = 22 which is not true.

Therefore, there is NO SOLUTION for the system of equations 6x + 2y = 10 and -6x - 2y = 12.

Added 4/22/2014 7:38:16 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/23/2014 1:25:47 PM]

The ordered pair (-1, -1) is a solution of the system -4x + 2y = 2 and x + y = -2. (A) True (B) false **Weegy:** True **User:** How many solutions exist for the system y = 2x + 5 and y = -0.2x - 4? (A) one solution (B) no solution (C) infinitely many solutions **Weegy:** solutions exist for the system y = 2x + 5 and y = -0.2x - 4: (C) infinitely many solutions **User:** How many solutions exist for the system, x + y = 1 and y = -x + 1? (A) one solution (B) no solution (C) infinitely many solutions **Weegy:** b. one solution (More)

Question|Asked by renaryoko

Expert Answered

Updated 4/22/2014 7:51:34 PM

3 Answers/Comments

y = 2x + 5

y = -0.2x - 4

Replace y in the second equation we have:

2x + 5 = -0.2x - 4

2x + 0.2x = -4 - 5

2.2x = -9

x = -9/2.2 = -90/22 = -45/11

y = -0.2(-9/2.2) - 4 = 9/11 - 4 = - 35/11

There is only ONE SOLUTION for the system of equations y = 2x + 5 and y = -0.2x - 4.

y = -0.2x - 4

Replace y in the second equation we have:

2x + 5 = -0.2x - 4

2x + 0.2x = -4 - 5

2.2x = -9

x = -9/2.2 = -90/22 = -45/11

y = -0.2(-9/2.2) - 4 = 9/11 - 4 = - 35/11

There is only ONE SOLUTION for the system of equations y = 2x + 5 and y = -0.2x - 4.

Added 4/22/2014 7:48:05 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/22/2014 7:57:21 PM]

x + y = 1

y = -x + 1

Replace y in the first equation we have:

x + (-x + 1) = 1

x - x + 1 = 1

0 = 0

therefore there are infinitely many solutions for the system x + y = 1 and y = -x + 1.

y = -x + 1

Replace y in the first equation we have:

x + (-x + 1) = 1

x - x + 1 = 1

0 = 0

therefore there are infinitely many solutions for the system x + y = 1 and y = -x + 1.

Added 4/22/2014 7:51:34 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/22/2014 7:57:28 PM]

Solve the system.
y = -1/3 x + 2 and x + 3y = 3: (A)(0, 1)
(B) (1, 0)
(C) (3, 1/3)
(D) (3/2, 0)
(E) no solution

Question|Asked by renaryoko

Not Answered

Updated 4/22/2014 1:52:50 PM

1 Answer/Comment

y = -1/3 x + 2;

3y = -x + 6;

x + 3y = 6;- >(1);

x + 3y = 3;->(2);

There is no solution for the above equations.

3y = -x + 6;

x + 3y = 6;- >(1);

x + 3y = 3;->(2);

There is no solution for the above equations.

Added 4/22/2014 1:52:50 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/22/2014 1:56:55 PM]

27,901,179

questions answered

There are no comments.